2021
DOI: 10.1371/journal.pntd.0008965
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerca volvulus and epilepsy: A comprehensive review using the Bradford Hill criteria for causation

Abstract: Background The possibility that onchocerciasis may cause epilepsy has been suggested for a long time, but thus far, an etiological link has not been universally accepted. The objective of this review is to critically appraise the relationship between Onchocerca volvulus and epilepsy and subsequently apply the Bradford Hill criteria to further evaluate the likelihood of a causal association. Methods PubMed and gray literature published until September 15, 2020, were searched and findings from original researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 106 publications
(217 reference statements)
3
86
0
1
Order By: Relevance
“…In recent years, the association between onchocerciasis and epilepsy has been clearly established in many epidemiological studies [ 19 ]. Moreover, these studies showed the usefulness of the OAE case definition for identifying hotspots of high ongoing O. volvulus transmission [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the association between onchocerciasis and epilepsy has been clearly established in many epidemiological studies [ 19 ]. Moreover, these studies showed the usefulness of the OAE case definition for identifying hotspots of high ongoing O. volvulus transmission [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the above studies suggest that O. volvulus infection is able to trigger epilepsy (Colebunders et al, 2021), the data do not demonstrate causality. Therefore, the involvement of an alternative pathogen cannot be excluded (Table 1).…”
Section: Research Updatementioning
confidence: 79%
“…A recent systematic review using the Bradford Hill criteria for causality identified O. volvulus as the most likely trigger of nodding syndrome and other forms of onchocerciasis-associated epilepsy (OAE) (Colebunders et al, 2021). Indeed, high prevalence of OAE is observed in onchocerciasis-endemic areas with high rates of O. volvulus transmission and low (Mukendi et al, 2019) or no (Lenaerts et al, 2018) coverage of community-directed treatment with ivermectin (CDTI).…”
Section: Research Updatementioning
confidence: 99%
See 1 more Smart Citation
“…However, so far mental health problems caused by onchocerciasis-associated epilepsy have not been internationally recognized. Given the strong epidemiological evidence for the association between onchocerciasis and epilepsy, onchocerciasis-associated epilepsy should be considered as one of the clinical presentations of onchocerciasis [ 12 ]. For those who still do not want to recognize this, onchocerciasis-associated epilepsy should be considered as new NTD because it only occurs in tropical areas and is a neglected public health problem.…”
Section: How To Tackle This Situation?mentioning
confidence: 99%